2013
DOI: 10.1021/bm400862m
|View full text |Cite
|
Sign up to set email alerts
|

From Invisible Structures of SWCNTs toward Fluorescent and Targeting Architectures for Cell Imaging

Abstract: Single-walled carbon nanotubes (SWNTs) are unique nanostructures used as cargo systems for variety of diagnostic and therapeutic agents. For taking advantage of these structures in biological processes, they should be visible. Therefore, fluorescence labeling of SWCNTs with various probes is a significant issue. Herein, we demonstrate a simple approach for cell specific imaging and diagnosis by combining SWCNTs with a copolymer poly(para-phenylene) (PPP) containing polystyrene (PSt) and poly(ε-caprolactone) (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 90 publications
0
18
0
Order By: Relevance
“…Dose dependent cytotoxic effect of C. officinalis extracts, niosomes and phyto-niosomes were determined via 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assays [37]. Cells were seeded out in 96-well-tissue plates in a volume of 200 µL and cultivated three days at 37 ºC, 5.0% CO 2 and 100% air humidity until reaching confluence.…”
Section: Cytotoxicitymentioning
confidence: 99%
“…Dose dependent cytotoxic effect of C. officinalis extracts, niosomes and phyto-niosomes were determined via 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assays [37]. Cells were seeded out in 96-well-tissue plates in a volume of 200 µL and cultivated three days at 37 ºC, 5.0% CO 2 and 100% air humidity until reaching confluence.…”
Section: Cytotoxicitymentioning
confidence: 99%
“…The relevance of amide group in glycine amide derivatives as novel Vascular Adhesion Protein‐1 inhibitors have also been reported by Yamaki et al . Moreover, reports on phenylene derivatives showing therapeutic effects include chalcogen functionalized phenylene derivative 1,4‐phenylene bis(methylene) selenocyanate (p‐XSC) and poly(p‐phenylene) that are indeed widely used for various biological applications through enhanced interaction with the target sites …”
Section: Introductionmentioning
confidence: 70%
“…Ag et al, for example, noncovalently functionalized SWCNTs with a fluorescent copolymer, poly(para-phenylene), with polystyrene and PCL side chains to obtain fluorescent SWCNT probes. 190 They then conjugated folic acid to target the HeLa cells in culture (Figure 8). In addition, Hu et al demonstrated that SWCNTs functionalized with a fluorescent naphthalenediimide moiety show good solvability in both organic and aqueous solvents, are biocompatible, and can be functionalized further through secondary reactions.…”
Section: Bioimagingmentioning
confidence: 99%
“…Schematic representation of conjugation process and cell specific imaging. Reprinted (adapted) with permission from American Chemical Society 190. Copyright (2013).…”
mentioning
confidence: 99%